Automated fan speed control system / Ahmad Shahrizal Alluwi - Alluwi, Ahmad Shahrizal (2018)
This paper presents the design of automated fan speed control system. The method to develop this kind of fan is divided into two parts which are hardware and software development. The speed control system is accomplished using relay module, ultrasonic sensor and temperature sensor. The speed control is automated according to the room temperature. The automated fan speed control system is successfully designed and developed.